Occurrence and Origin of H2S from Volcanic Reservoirs in Niudong Area of the Santanghu Basin, NW China. (2nd June 2019) - Ma, Xiangxian; Zheng, Guodong; Liang, Minliang; Xie, Dianhe; Martinelli, Giovanni; Sajjad, Wasim; Xu, Wang; Fan, Qiaohui; Li, Liwu; Du, Li; Zhao, Yidong
Abstract : A series of samples including natural gas, formation water, and rocks were collected from volcanic rock reservoirs in the Niudong area of the Santanghu Oilfields and analyzed for their mineral and/or chemical compositions and sulfur and carbon isotopes in order to investigate the occurrence and origin of hydrogen sulfide (H2 S). H2 S was mostly dissolved in the formation water along with petroleum production in the study area. The δ 34 S values of on-well H2 S samples varied in a range of 9.2‰ to 20.5‰, probably indicating thermochemical sulfate reduction (TSR) and/or thermal decomposition of organic sulfur-bearing compounds (TDS) as the genetic process for H2 S. However, the chemical composition of formation waters from the Kalagang Formation (C2 k ) and their coefficient of desulfurization also revealed that TSR could be the main principle for H2 S formation. Considering the regional geological background, especially the tectonic structures and thermal evolution features of the basin, it was concluded that H2 S in the study area was dominantly produced by thermal genesis with TSR as a domain through interactions between hydrocarbons and aqueous sulfate dissolved from sulfate minerals.